Study of Urothelial Neoplasm in Central India With Reference To WHO/ISUP Grading - Vivek Khare; Vivek Kumar Jain; Rajendra Tantuway (International Journal of Medical Research and Review, 2013)
Introduction: Urothelial carcinoma is the most common bladder cancer, is often described as a polyclonal field change defect with frequent recurrence due to heightened potential for malignant transformation. Urothelial neoplasm runs the gamut from small benign neoplasm that may never recur to tumors of lower indeterminate malignant potential to lesions that invade the bladder wall and metastasize frequently. Hence histologic grading of these tumors to predict behavior has been subject of great debate as there is poor inter - observer reproducibility and no uniformity.Material and Methods: The present study was carried out in the Department of Pathology, L.N. Medical College, Bhopal, India. It was both a prospective and a retrospective study of 80 patients whose urinary bladder biopsy were studied.Result: 80 cases reported out of which 20 were transitional papilloma, 52 were cases of ransitional cell carcinoma and 8 cases were of squamous cell carcinoma. The majority of tumours are present in age group of 50-80 years.Discussion: Although World Health Organization classification system is most commonly used grading system but lack of detailed histological criteria motivated WHO and ISUP to publish a consensus classification for urothelial neoplasm of urinary bladder. The majority of the cases in this study belonged to the histologic grades of papillary carcinoma of low grade which corresponds to the WHO classification of transitional cell carcinoma grade II.